Factors affecting the prevalence of mortality associated with pneumonia in a flock of Muzaffarnagari sheep - Mandal, Ajoy; Barua, S; Rout, P K; Roy, R; Prasad, H; Sinha, N K; Sharma, N (The Indian Journal of Animal Sciences, 2005)
Data of 4628 lambs of Muzaffarnagri ewes were analyzed for 25 years (1978 to 2002), to identify the major causes of perinatal and postnatal mortality associated with pneumonia alongwith factors affecting the incidence of mortality. The least-squares for the overall mortality up to 1 year of age of the flock were 12.6%. The overall pre- and post-weaning mortality averaged6.6 and 6.0% respectively. Pneumonia accounted for the highest proportion (29.9%) of all deaths. The main causes of early lamb mortality i.e. within 15 days of birth were pneumonia followed by mismothering exposures. The period of birth had significant effects on lamb losses due to pneumonia in all age groups. while the season of birth had a signiticant influence on mortality to 3 months of age. The lambs born during October-November succumbed significantly due to pneumonia than those born in March-April. The lamb mortality was significantly (P&lt0.01) higher in males at post-weaning stages than their female counterparts. Multiple born lambs had a higher mortality rate (0.97%) within 3 days of birth, compared to single born lambs. Besides, the linear regression of lamb birth weight and dam weight at lambing was highly significant on lamb mortality associated with pneumonia in all age groups.